2021
DOI: 10.2147/opth.s321110
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Visual Field Border

Abstract: The aim of the study was to determine the physiological temporal visual field border, based on theoretical calculations and by perimetric examination itself. Materials and Methods: A perimetry test was performed on 15 healthy subjects -seven women (27-30 years old) and eight men (28-46 years old), all of whom had healthy eyes with a visual acuity value of 1.0. The visual field was evaluated using a Medmont M700 with nasal displacement of the fixation point of 40 degrees. In total, 179 examined points of visual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…Na základě geometrické optiky a biometrických údajů měřeného oka jsme v předchozí práci zjišťovali, pod jak velkým úhlem vstupující paprsky jsou ještě schopny do-padnout na zadní pól oka. Prošly paprsky vstupující do oka pod úhly do 102 stupňů při šíři pupily 4,64 mm (Obrázek 3) [9].…”
Section: Diskuzeunclassified
See 1 more Smart Citation
“…Na základě geometrické optiky a biometrických údajů měřeného oka jsme v předchozí práci zjišťovali, pod jak velkým úhlem vstupující paprsky jsou ještě schopny do-padnout na zadní pól oka. Prošly paprsky vstupující do oka pod úhly do 102 stupňů při šíři pupily 4,64 mm (Obrázek 3) [9].…”
Section: Diskuzeunclassified
“…Pro nesoulad v hodnotách temporální hranice zorného pole jsme v předchozí práci provedli verifikaci jejich hodnot pomocí subjektivního vyšetření a tento výsledek jsme ověřili i teoretickým výpočtem. U zdravých osob jsme zjistili temporální hranice zorného pole ve 110 stupních [9]. Rovněž nás zajímalo, jak je to se vzdálenou nasální částí zorného pole, která je prakticky nepoužíva-ná.…”
unclassified
“…With a normal visual field tested by the fast threshold glaucoma program (nasal to 50, temporal to 22 degrees), distal nasal periphery visual field changes were found in the entire cohort. 14 In our previous study, where we investigated the relationship between RNFL and pathological IOP, we demonstrated peripapillary RNFL damage in inferior-temporal (1), superior-temporal (4), superior-nasal (5), and inferior-nasal (8) segments in pathological intraocular pressure (IOP). 15 As vessel density (VD) also makes a significant contribution to the total value of RNFL, we performed statistical correction of VD from RNFL using the partial correlation coefficient, the most significant correlation of these parameters was found in segments 5 and 8.…”
Section: Introductionmentioning
confidence: 99%
“…With a normal visual field tested by the fast threshold glaucoma program (nasal to 50, temporal to 22 degrees), distal nasal periphery visual field changes were found in the entire cohort. 14 …”
Section: Introductionmentioning
confidence: 99%